A STUDY OF LOGICAL-MATHEMATICAL THINKING FROM MULTIPLE INTELLIGENCES FRAMEWORK - Ferrándiz, Carmen; Bermejo, Rosario; Sainz, Marta; Ferrando, Mercedes; Prieto, Maria Dolores (Anales de Psicología / Annals of Psychology, 2008)
The aim of this work is two fold: a) to study the mathematical-logic reasoning of a sample of Preschool and Primary education pupils; and b) to study the relationship between logical-mathematical intelligence and academic intelligence. In addition, we study gender and age differences. Two hundred and ninety-four pupils (aged 4 to 8) from three different schools in Murcia and Alicante (Spain) took part in this research. The instruments used were: a) seven activities oriented towards assessing multiple intelligences (linguistic, logical-mathematical, spatial, bodily-kinaesthetic, musical and naturalist intelligence; and b) BADyG (Battery of Differential and General Aptitudes), the aim of which is to assess the academic intelligence. The results showed statistically significant differences in mathematical-logical intelligence, with primary school pupils attaining higher scores. However, the data did not show statistically significant differences according to gender. Finally, it is necessary to pointed out that to assess logical reasoning using two different measures (dynamic, using multiple intelligences, versus psychometric) it very useful in order to achieve more complete information.